Systemic amyloidosis with gastrointestinal tract involvement: Histologic features of 93 cases - Banu BİLEZİKÇİ and Beyhan DEMİRHAN and; an N. HABERAL and; t BOYACIOĞLU and; l GÜNGEN (Turkish Journal of Gastroenterology, 2019)
-